2019
DOI: 10.1007/s40279-019-01176-9
|View full text |Cite|
|
Sign up to set email alerts
|

Injury Risk in New Zealand Rugby Union: A Nationwide Study of Injury Insurance Claims from 2005 to 2017

Abstract: Objectives The Accident Compensation Corporation is a compulsory, 24-h, no-fault personal injury insurance scheme in New Zealand. The purpose of this large-scale retrospective cohort study was to use Accident Compensation Corporation records to provide information about rugby injury epidemiology in New Zealand, with a focus on describing differences in risk by age and gender. Methods A total of 635,657 rugby injury claims were made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
3
27
1
Order By: Relevance
“…2 In New Zealand (NZ), concussions accounted for 3.1% of all injuries in community rugby across all age groups, as reported by the Accident Compensation Corporation (ACC) from 2005 to 2017. 3 From 2012–2016, an increase in moderate-to-severe concussions was observed, making it the third most common ACC injury entitlement claim in rugby. 4 Research in schoolboy rugby reports concussion rates of 6–8 concussions per 1000 player match hours.…”
Section: Introductionmentioning
confidence: 99%
“…2 In New Zealand (NZ), concussions accounted for 3.1% of all injuries in community rugby across all age groups, as reported by the Accident Compensation Corporation (ACC) from 2005 to 2017. 3 From 2012–2016, an increase in moderate-to-severe concussions was observed, making it the third most common ACC injury entitlement claim in rugby. 4 Research in schoolboy rugby reports concussion rates of 6–8 concussions per 1000 player match hours.…”
Section: Introductionmentioning
confidence: 99%
“…The elite rugby player group was at systematically higher risk of sustaining injuries during their playing careers than the non-contact sports player group; higher percentages of the elite rugby group were hospitalised because of a sporting injury and had a surgery related to an injury that occurred during participation in their sport than either the community rugby group or the non-contact sport player group. The proportions of the types of self-reported injuries were consistent with medically diagnosed injuries due to playing rugby from 2005 to 2017 recorded via the NZ national Accident Compensation Corporation claims [ 20 ].…”
Section: Discussionmentioning
confidence: 75%
“…Analyzing the most common body region of injury, the statistically significant difference between Polish and French players was noticed in the frequency of the left shoulder injury which was more often for the formers. According to research on sports injuries in professional rugby [ 26 , 27 ], there has been an increase in the frequency and severity of shoulder injuries among rugby players in recent years and the reason is that the game has become more aggressive and intense [ 26 , 28 ]. A descriptive epidemiological study performed in all players licensed in the French Rugby Union showed that shoulder injury was significantly more frequent in senior and junior players, injuries mainly occurred during a match in the middle of the season and the main mechanism was tackling [ 29 ].…”
Section: Discussionmentioning
confidence: 99%